Comparative lifecycle cost and sustainability assessments between very-light rail and bus-rapid transit - David Boateng Yeboah; Sakdirat Kaewunruen (Transportation Research Interdisciplinary Perspectives, 2025)
This paper presents a comprehensive lifecycle environmental and economic sustainab ility of two medium-capacity urban transit systems − Very Light Rail (VLR) and Bus Rapid Transit (BRT). Considering identical systems’ functional unit, real-world case studies of Coventry Very Light Rail (CVLR) project and Cambridgeshire Guided Busway (CGB) were evaluated as representatives of the VLR and BRT systems, respectively. The LCA’s quantified greenhouse gas emissions across all phases, from raw materials to recycling and decommissioning. CVLR exhibited 48% higher total lifecycle GHG emissions compared to CGB, with substantial differences across lifecycle phases. Emissions were significantly higher for CVLR during material production, construction and transport, which is largely due to associated production and manufacturing of ultra high-performance fibre-reinforced concrete and complex construction methods. CVLR also had 21% higher operational emissions attributed to a larger required depot size and an additional station. Our new findings exhibit that BRT system is more cost- and carbon-effective.